2021
DOI: 10.1002/chem.202101061
|View full text |Cite
|
Sign up to set email alerts
|

Radiochromic Hydrogen‐Bonded Organic Frameworks for X‐ray Detection

Abstract: Porous materials have been investigated as efficient photochromic platforms for detecting hazardous radiation, while the utilization of hydrogen bonded organic frameworks (HOFs) in this field has remained intact. Herein, two HOFs were synthesized through self-assembly of tetratopic viologen ligand and formic acid (PFC-25, PFC-26), as a new class of "allorganic" radiochromic smart material, opening a gate for HOFs in this field. PFC-26 is active upon both X-ray and UV irradiation, while PFC-25 is only active up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 76 publications
(16 reference statements)
0
25
0
Order By: Relevance
“…In addition, there are plenty of supramolecular interactions (Figures S7 and S8), such as anion−π interactions, O–H···N H-bonds, C–H···N H-bonds, O–H···O H-bonds, among [Co­(CN) 6 ] 3– anions, free or/and coordinated H 2 O molecules, and bcbp ligands in the D–A hybrid architecture, which consolidate the D–A hybrid structure. Moreover, the anion−π interactions between Co­(CN) 6 3– anions and bcbp ligands in the D–A hybrid architecture may provide electron-transfer pathways to realize the reversible dual photochromism. ,,, …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, there are plenty of supramolecular interactions (Figures S7 and S8), such as anion−π interactions, O–H···N H-bonds, C–H···N H-bonds, O–H···O H-bonds, among [Co­(CN) 6 ] 3– anions, free or/and coordinated H 2 O molecules, and bcbp ligands in the D–A hybrid architecture, which consolidate the D–A hybrid structure. Moreover, the anion−π interactions between Co­(CN) 6 3– anions and bcbp ligands in the D–A hybrid architecture may provide electron-transfer pathways to realize the reversible dual photochromism. ,,, …”
Section: Resultsmentioning
confidence: 99%
“…All of them indicated that the photochromic behavior involves only electron transfer because no composition loss or skeleton change was observed in irradiated samples. According to refs and , the appropriate distance between the acceptor and donor is quite necessary to give rise to electron transfer upon X-ray and UV irradiation (<3.8 Å for UV photochromism and ∼4 Å for X-ray photochromism). As shown in Figures S7 and S8, there are strong anion−π interactions between electron donor Co­(CN) 6 3– anions and electron acceptor bipyridyl units.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The successful preparation of a stable HOF, tecton-1 ( L2 ), in 1997 by Wuest led to a rapid expansion of experimental and theoretical investigations in this field . Since then, numerous HOFs with diverse structures and unique properties have been reported at an astonishing pace, and this has led to the successful implementation of these crystalline porous materials in applications that include gas storage and separation, chiral separation, chemical sensing, proton conduction, radiation detection, water remediation, antibacterial activity, enzyme encapsulation, and catalysis. , …”
Section: Introductionmentioning
confidence: 99%